CONNOTATIVE MEANINGS IN THE SELECTED ARIANA GRANDE’S SONG LYRICS - Matius Mandey, Philif; Kurniati, Nur Utami Sari'at; Permatasari, Shita Dewi Ratih (Universitas Pakuan, 2024)
This research is entitled “Connotative Meaning in Song Lyrics on Ariana Grande’s Album”. The purpose of this research is to identify the connotative meaning in the song lyrics on several Ariana Grande’s album, to classify the types of connotations, and to explain the connotative meaning. This research uses descriptive method. In collecting data, the writer focuses on words, phrases, and clauses that have connotative meanings and classifies them based on Olikova’s theory in Stylistic and Social Cognition (2007) which classifies connotative meanings into positive and negative meanings. The result of this research is that there are thirty words, twenty phrases, and three clauses that contain connotative meanings in the song lyrics, and the connotative meanings have variations in their descriptions.